Banten Coastal Sea Fence: Media Framing and the Potential for Socio-Religious Movements - Iman Mukhroman; Ivan Issa Fathony (UPT Publikasi Ilmiah UNISBA, 2025)
This research analyzes online media framing of the 30.16-kilometer sea fence case in Banten that emerged in early 2025. Using Robert Entman's framing model, this research specifically compares the way detik.com and Republika Online framed the issue and explores its potential to shape social, religious, or combined movements. The primary data consisted of 16 news articles (8 from each media) published in January 2025. The findings show significant differences in the narrative construction of the two media: detik.com tends to frame the case as a challenge to the authority of the state that requires government assertiveness, while Republika Online emphasizes the dimension of social injustice experienced by coastal communities. There is a strong potential for social movements in the framing of both media, but the potential for religious movements only appears implicitly in Republika Online, while detik.com almost completely ignores this dimension. This research contributes to the understanding of the role of media in shaping opportunities for socio-religious mobilization in Indonesia, and shows how media framing reflects their respective characters, audience segmentation, and ideological orientation.